Nearpod Integration in Science Learning for Junior High School Students: A Review - Ramadhan, Awaludin Pandu; Fibriana, Fidia (Jurnal Pijar Mipa, 2025)
Learning media represents a significant innovation in educational technology, with Nearpod emerging as a valuable tool for enhancing interactive science education in junior high schools. The current generation of students often experiences boredom during traditional learning methods, necessitating the adoption of engaging platforms like Nearpod to facilitate effective material delivery. This study aims to evaluate the application of Nearpod in teaching energy concepts within junior high school science curricula. Employing a Systematic Literature Review (SLR) methodology guided by the PRISMA protocol, this research involved a comprehensive literature search using the Google Scholar database, supported by the Publish or Perish (PoP) application. Out of 386 identified research papers, 11 met the criteria for detailed analysis. The analysis reveals that the integration of Nearpod in junior high school science education is relatively underexplored, especially in topics such as energy. However, findings indicate that Nearpod is an effective medium for fostering engagement, critical thinking, and learning outcomes. These results encourage science educators to incorporate Nearpod into inquiry-based or project-based learning to support more interactive, student-centered instruction. The review is limited to open-access studies conducted in Indonesia between 2015 and 2025, focusing solely on junior high school science education.